Pepper and Power: Portuguese Influence on Spice Trade in 15th-16th Century in Aceh - Cut Meurah Habibur Rahman (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2024)
Abstract: The arrival of the Portuguese in the Northern Sumatra during the 15th-16th centuries led to substantial changes in trade dynamics, particularly impacting Aceh. The consolidation of the Pasai and Pidie Kingdoms into the Kingdom of Aceh, coupled with diplomatic connections with the Ottoman Sultanate, strategically addressed the Portuguese presence. By using qualitative methods and adopting a chronological historiographical approach, this scholarly presentation systematically outlines the development of the trade conflict between Aceh and the Portuguese. Utilizing primary sources such as the travel accounts of Tome Pires, Fernao Pinto, and Alexander Hamilton, complemented by a range of secondary sources, the study dissects the geopolitical landscape and intricacies of conflicting interests that defined the Aceh-Portuguese relations. The analysis highlights the essential changes in trade dynamics and spice trade induced by the presence of the Portuguese, while illustrating Aceh's strategic efforts in responding to these changes. The research outcomes underscore the significance of interregional collaborations, exemplified by the unity of Aceh and diplomatic partnerships with the Ottoman Empire, as strategic measures in facing the challenges of global trade. This study not only furnishes a comprehensive understanding of Aceh's strategic positioning but also delves into the multifaceted complexities of conflicting interests during the specified historical epoch. Consequently, this research significantly contributes to our understanding of historical and geopolitical interactions in the region in the past. Lada dan Kekuasaan: Pengaruh Portugis terhadap Perdagangan Rempah pada Abad ke 15-16 di Aceh Abstrak: Masuknya Portugis ke kawasan Sumatra Timur pada abad ke-15 hingga ke-16 membawa transformasi signifikan dalam tatanan perdagangan, terutama di Aceh. Proses penyatuan Kerajaan Pasai dan Pidie menjadi Kerajaan Aceh, serta kerjasama dengan Kesultanan Ottoman, menjadi respons strategis terhadap penetrasi Portugis. Artikel ini, menggunakan metode kualitatif dan pendekatan historiografi kronologis, menguraikan perkembangan perang dagang antara Aceh dan Portugis dan keterlibatan perdagangan di Selat Malaka. Dengan memanfaatkan sumber-sumber primer seperti catatan perjalanan Tome Pires, Fernao Pinto, dan Alexander Hamilton, bersama dengan dukungan dari sumber-sumber sekunder lainnya, penelitian ini mengupas peta geopolitik dan konflik kepentingan yang menjadi ciri hubungan Aceh-Portugis. Analisis ini menyoroti esensialnya perubahan dalam dinamika perdagangan rempah yang disebabkan oleh kehadiran Portugis, sekaligus menggambarkan upaya strategis Aceh dalam menanggapi perubahan tersebut. Hasil penelitian menunjukkan pentingnya kerja sama antar wilayah seperti kesatuan Aceh dan kerjasama dengan Ottoman dalam merespons tantangan perdagangan global. Kajian ini menawarkan pemahaman mendalam tentang peran strategis Aceh dan kompleksitas konflik kepentingan yang terjadi selama periode tersebut. Dengan demikian, penelitian ini memberikan kontribusi signifikan terhadap pemahaman kita tentang interaksi sejarah dan geopolitik di kawasan tersebut pada masa lampau.